'If Not Me, Then Who?' Examining Engagement with Holocaust Memorial Day Commemoration in Britain. Issue 1 (2nd January 2018) - Richardson, John E.
ABSTRACT: This article explores what motivates ordinary people to become involved with commemorating Holocaust Memorial Day (HMD). While there is an expanding academic literature on HMD, public commemoration, and the memory work (and politics) of remembrance, a great deal of this commentary and analysis is offered from the firsthand perspective of academics writing about large-scale public memorial or museum projects. There is, in contrast, very little published that examines small-scale public participation with HMD, including why people get involved in organizing their own commemorative activities. Since 2005, the Holocaust Memorial Day Trust has been responsible for organizing and promoting HMD commemoration in Britain, and as part of this brief, they organize free workshops across the UK for people interested in organizing an activ ity to mark HMD. This article analyzes interviews with the organizers and participants of three workshops that took place during the buildup to HMD 2016. In this article, I focus in particular on the ways that interviewees orientate to questions of conscience and the ways in which their personal and political values accord with the aims of HMD. My article suggests that the pedagogical and political potentials of HMD are more varied than academic analysis has thus far suggested and that further work is needed to explore the engagement of ordinary people in HMD commemoration.